Physico-chemical and sensorial assessment of muscovado produced by selected mills in Laua-an, Antique - Mediavilla, Richelle Tejado (2009.)
Physico-chemical and sensorial assessment of muscovado produced in selected mills in Laua-an, Antique were conducted.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Muscovado